Zdravilne rastline za dermalno uporabo - nova znanja in trendi - Kočevar Glavač, Nina (Farmacevtski vestnik, 2021)
Herbal preparations represent an important approach for the prevention and treatment of acute and chronic skin diseases, as well as for skin care, both as skin conditioning agents and supportive care in skin diseases. Today, medicinal plants for dermal use have also been researched extensively at a clinical level, which is considered high-quality evidence in terms of effectiveness and represents the basis for their successful evidence-based medicinal use. The article reviews medicinal plants for use in wounds, acne and warts, with an emphasis on new clinical studies published after 2010.
Keywords: dermalna uporaba; Koža; rastlinski pripravki; Zdravilne rastline